MIGRANT’S THE FACELESS & NAMELESS ECONOMIC DRIVER AMID COVID19 - Baijayanti Ghosh (Research Parks Publishing LLC, 2020)
India is least urbanized among top ten economies of the world. Recent years have seen a spurt in development in various sectors, and a transition of work force out from agriculture to other sectors; this coupled with jobless growth has made a huge flow of unskilled labours from various states. The so called Migrants, the faceless nameless people who are the real driver’s of our economy. They move from their states to other places in search of a livelihood, to sustain and survive, and contribute to our economy, in a subtle way we never actually thought off. There are many reasons for this, regional disparities, employment opportunities, are most prominent. Never the less their invisible hands are more needed than ever now, as we unlock and head towards economic activity, but maybe we have failed the migrant labours as a society. India’s informal workforce is made up of 80% migrant workers, and yet we haven’t given them the credibility they deserve. May be it’s time now, to acknowledge who they are, and what they are, else we risk losing the major workforce of our country, and face unprecedented economic consequences.